1995
DOI: 10.1002/jor.1100130417
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the ankle anterior drawer test for anterior talofibular ligament injuries

Abstract: The effect of sectioning the anterior talofibular ligament on the load-displacement behavior of the ankle was evaluated in vitro during the anterior drawer test using the flexibility approach. Controlled forces were applied across the ankle joint in the anterior-posterior direction, and the resulting displacements were measured at four flexion angles (10 degrees of dorsiflexion, neutral, and 10 degrees and 20 degrees of plantar flexion). The anterior talofibular ligament then was sectioned, and the anterior-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
59
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 22 publications
6
59
0
Order By: Relevance
“…Several investigators have reported similar increases in laxity after ATFL or CFL sectioning (Kjaersgaard-Andersen et al 1991, Johnson and Markolf 1983, Hollis et al 1995, Tohyama et al 1995, but have reached widely varying conclusions regarding the most sensitive flexion angle for testing. Apart from differences in experimental setup which could, in part, explain the different conclusions reached, the fact remains that individual variations in ligament orientation (Burks and Morgan 1994) may cause different laxity patterns in different patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several investigators have reported similar increases in laxity after ATFL or CFL sectioning (Kjaersgaard-Andersen et al 1991, Johnson and Markolf 1983, Hollis et al 1995, Tohyama et al 1995, but have reached widely varying conclusions regarding the most sensitive flexion angle for testing. Apart from differences in experimental setup which could, in part, explain the different conclusions reached, the fact remains that individual variations in ligament orientation (Burks and Morgan 1994) may cause different laxity patterns in different patients.…”
Section: Discussionmentioning
confidence: 95%
“…However, some studies have concluded that the laxity increase resulting from ATFL injury is greater in dorsiflexion than in plantarflexion (Johnson andMarkolf 1983, Hollis et al 1995), whereas others advocate plantarflexion as the best testing position to detect isolated ATFL injury (Tohyama et al 1995). Kjzrsgaard-Andersen et al concluded that the laxity increase after an isolated ATIT injury are similar throughout the entire flexion range ( I 991).…”
Section: Discussionmentioning
confidence: 99%
“…L ateral ligament stress testing after an inversion ankle sprain is used to identify the presence of increased laxity within the talocrural and subtalar joints (ankle complex) when compared with the contralateral ankle. 1 This assessment commonly involves the anterior drawer and inversion tests [2][3][4] and is performed by applying an anteriorly directed force or inversion torque to the foot. 5 In the biomechanical literature, researchers [6][7][8] have shown the anterior talofibular ligament (ATFL) is the major ligamentous structure preventing forward subluxation of the talus and the calcaneofibular ligament (CFL) is the primary restraint of talar inversion.…”
mentioning
confidence: 99%
“…9,10 Increases in ankle-complex motion with isolated and combined sectioning of the ATFL and CFL have been reported extensively. 2,8,[10][11][12] General consensus in the literature is that measuring the relationship between ligament damage and joint laxity by simulating ligamentous injury in the cadaver specimen improves our understanding of joint motion and the effect ligament damage has on producing instability in the ankle-subtalar complex. Thus, objective documentation that describes change in the passive mechanical properties of the ankle complex with lateral ligament injury could be important in the differential diagnosis of these injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation